2006
DOI: 10.1111/j.1542-4758.2006.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Large variations in prescriptions of gastrointestinal medications in hemodialysis patients on three continents: The Dialysis Outcomes and Practice Patterns Study (DOPPS)

Abstract: Little is known about proton pump inhibitor (PPI) or H(2) receptor antagonist (HA) prescription patterns or regarding use of predictors in hemodialysis patients. Proton pump inhibitor and HA prescribing patterns were investigated in 8628 hemodialysis patients from seven countries enrolled in the prospective, observational Dialysis Outcomes and Practice Patterns Study. Logistic regression examined predictors associated with PPI and HA use, adjusting for age, sex, country, time with end-stage renal disease, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Interestingly, estimates that appeared to be obtained from the same cohort of patients were not always similar. Bailie et al (21) reported a prevalence of 9% (95% CI, 8.9 to 10.1%) in DOPPS I from 1996 to 2001, whereas Elder et al (20) reported an estimate of 28% (95% CI, 27.1 to 29.3%) from the same database as of 2000. These variable prevalence estimates did not correlate with time period, dialysis vintage, or sample size (data not shown).…”
Section: Patterns Of Opioid Usementioning
confidence: 96%
See 3 more Smart Citations
“…Interestingly, estimates that appeared to be obtained from the same cohort of patients were not always similar. Bailie et al (21) reported a prevalence of 9% (95% CI, 8.9 to 10.1%) in DOPPS I from 1996 to 2001, whereas Elder et al (20) reported an estimate of 28% (95% CI, 27.1 to 29.3%) from the same database as of 2000. These variable prevalence estimates did not correlate with time period, dialysis vintage, or sample size (data not shown).…”
Section: Patterns Of Opioid Usementioning
confidence: 96%
“…Five were from the United States (1,13,17,24,25), one was from Canada (7), and one was from Belgium (19). The remaining three included cross-sections of patients from between 7 and 12 countries (Dialysis Outcomes and Practice Patterns Study [DOPPS] I and II) (20,21,23). Two of the DOPPS I studies reported on similar cohorts of patients (20,21) (Figure 2).…”
Section: Patterns Of Opioid Usementioning
confidence: 99%
See 2 more Smart Citations
“…Chan A, Untch M, Petruzelka L, et al: Navelbine and trastuzumab combination as first line therapy for HER 2-overexpressing metastatic breast cancer (HER2 ϩ MBC) is a highly active and safe regimen: Final results of multinational trial. Presented at 25th Annual San Antonio Breast Cancer Symposium, December [3][4][5][6]2003 1 The authors suggest that we have significantly underestimated the level of cardiac monitoring and overestimated the level of "off-label" trastuzumab use. They also question our interpretation of the findings in relation to the longer duration of trastuzumab therapy in actual practice versus that observed on trial.…”
mentioning
confidence: 99%